TIME SERIES MODELING FOR FORECASTING WHEAT PRODUCTION OF PAKISTAN - M. Amin; M. Amanullah; A. Akbar (Journal of Animal and Plant Sciences, 2014)
Wheat is the main agriculture crop of Pakistan.  For country planning, forecasting is the main tool for predicting the production of wheat to determine the situation what would be the value of production coming year. In this research, we developed time series models and best model is identified for the objective to forecast the wheat production of Pakistan. In this research large time periods i.e. 1902-2005 data was used. Various time series models are fitted on this data using two software’s JMP and Statgraphics. We have found that the best model is ARIMA (1, 2, 2).  On the basis of this selected model, we have found that wheat production of Pakistan would become 26623.5 thousand tons in 2020 and would become double in 2060 as compared in 2010.
Keywords: ARIMA; Time Series models; Wheat Production Forecasting